‘The televising of science is a process of television’: establishing Horizon, 1962–1967. - BOON, TIMOTHY (British Journal for the History of Science, 2015)
BBC Television's Horizon series, fifty years old on 2 May 2014, despite its significance to the history of the public culture of science, has been little studied. This microhistorical account follows the gestation and early years of the programme, demonstrating how it established a social and cultural account of science. This was a result of televisual factors, notably the determination to follow the format of the successful arts television programme Monitor. It illuminates how the processes of television production, with a handful of key participants – Aubrey Singer, Gerald Leach, Philip Daly, Gordon Rattray Taylor, Ramsay Short, Michael Peacock and Robert Reid – established the format of the programme. This occurred over seventeen months of prior preparation followed by three troubled years of seeking to establish a stable form. This was finally achieved in 1967 when the programme adopted a film documentary approach after extended attempts at making it as a studio-based magazine programme. The story has implications for understanding the social accounts of science that were circulating in the key decade of the 1960s.